The Study of Religiosity Impact on Family Cohesion in Hamedan - nahid babaei; esmaeil balali; asadollah naghdi; ahmad karimi (توسعه اجتماعی)
Due to the importance of cohesion in society, discussion of family cohesion is considered as one of the important institutions of society. It means feeling solidarity, relation and emotional commitment which family members have toward each other. The aim of this study is exploring the effect of religiosity on family cohesion among Hamedan families which have student in their family Durkheim, Epstein, Thomas and Lvyngr’s perspectives have been used as theoretical framework. The present study used survey method and data were collected using structured questionnaires completed by parents. A sample of 379 people using Cochran formula was selecred. Sampling method was multi-stage cluster sampling. Results showed that among the religiosity aspects, social representation aspect of religiosity has stronger relation with family cohesion. In addition, among the aspects of family cohesion, religiosity has stronger relation with family- related disputes and the weakest relation with political-related disputes.